Halal Food Fraud in Indonesia: A Sharia-Based Review and Strategic Solutions - Sholahuddin, Muhammad; Robbani Ridho, Muhammad; Asri Abdullah, Moha (Indonesian Journal of Islamic Economic Law, 2025)
This study investigates the phenomenon of halal food fraud in Indonesia, particularly focusing on its forms, drivers, and impact on Muslim consumer trust. This study employs a qualitative approach, utilizing a single case study method that focuses on the city of Surakarta (Solo), Central Java. The data presented herein was collected through a document analysis. The selection of Surakarta as a case study was predicated on its notable concentration of Muslim residents, its rapid growth in the culinary sector, and its status as a major center of Islamic education and culture in urban areas. The research findings revealed ten main forms of halal violations, including the covert use of haram ingredients, fake halal labeling, and improper handling of halal equipment. The prevalence of such fraudulent practices can be attributed to the overarching economic motivations inherent within a capitalist-secular system that places a higher value on profit than on ethical and religious obligations. The study also found significant erosion of Muslim consumer trust due to repeated violations, and demonstrated that non-Muslim business owners' lack of understanding of halal-haram values, coupled with weak law enforcement, exacerbates the problem. This study makes a significant contribution to the existing body of knowledge by offering a novel synthesis of moral, ideological, and legal perspectives on food fraud in Indonesia. The present study underscores the significance of systemic reform by proposing two levels of solutions: (1) short-term practical measures, such as digital tracking, halal literacy programs, and regulatory strengthening; and (2) long-term ideological transformation through the adoption of a comprehensive Islamic framework to ensure moral accountability in the food supply chain.